2018
DOI: 10.1159/000492924
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Retinal Pigment Epithelium Atrophy Subsequent to Anti-VEGF Therapy in Patients with Neovascular Age-Related Macular Degeneration

Abstract: Purpose: The aim of this study was to evaluate risk factors for the development of retinal pigment epithelium (RPE) atrophy in patients with neovascular age-related macular degeneration (nAMD). Procedures: This post hoc analysis of the prospective RESPONSE study includes 52 therapy-naive nAMD patients without baseline RPE atrophy, who were treated with ≥9 anti-vascular endothelial growth factor (VEGF) injections for ≥3 years. RPE atrophy was assessed via multimodal imaging. Baseline aqueous VEGF and serum comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Two publications reported atrophy outcomes using CFP, FA, and spectral-domain (SD) OCT from IVAN (The Inhibition of VEGF in Age-related choroidal Neovascularisation; Current Controlled Trials ISRCTN92166560). 10,27 Over 2 years, 30% of eyes demonstrated GA. 10 An analysis of 11,13e24 Color fundus photography and fluorescein angiography* HARBOR 12,25,26 Color fundus photography and fluorescein angiography IVAN 10,27 Color fundus photography, fluorescein angiography, and OCT RESPONSE 28 Color fundus photography, fluorescein angiography, SD OCT, FAF, and infrared imaging SEVEN-UP 29,30 Fluorescein angiography and FAF y TREX-AMD 31,32 SD OCT, FAF, and infrared imaging Chang et al (2015) 33 Color fundus photography and fluorescein angiography, FAF, and SD OCT Saito et al (2017) 34 Color fundus photography and short-wavelength autofluorescence Thavikulwat et al (2017) 35 Color fundus photography, fluorescein angiography, FAF, and SD OCT Zandi et al (2017) 36 FAF and SD OCT Mantel et al (2018) 37 Color fundus photography, fluorescein angiography, FAF, and SD OCT Mantel et al (2018) 38 Color fundus photography, fluorescein angiography, FAF, and SD OCT 13 Cohort study within CATT (N ¼ 1030; patients who completed 2 yrs of follow-up)…”
Section: Ivanmentioning
confidence: 99%
See 1 more Smart Citation
“…Two publications reported atrophy outcomes using CFP, FA, and spectral-domain (SD) OCT from IVAN (The Inhibition of VEGF in Age-related choroidal Neovascularisation; Current Controlled Trials ISRCTN92166560). 10,27 Over 2 years, 30% of eyes demonstrated GA. 10 An analysis of 11,13e24 Color fundus photography and fluorescein angiography* HARBOR 12,25,26 Color fundus photography and fluorescein angiography IVAN 10,27 Color fundus photography, fluorescein angiography, and OCT RESPONSE 28 Color fundus photography, fluorescein angiography, SD OCT, FAF, and infrared imaging SEVEN-UP 29,30 Fluorescein angiography and FAF y TREX-AMD 31,32 SD OCT, FAF, and infrared imaging Chang et al (2015) 33 Color fundus photography and fluorescein angiography, FAF, and SD OCT Saito et al (2017) 34 Color fundus photography and short-wavelength autofluorescence Thavikulwat et al (2017) 35 Color fundus photography, fluorescein angiography, FAF, and SD OCT Zandi et al (2017) 36 FAF and SD OCT Mantel et al (2018) 37 Color fundus photography, fluorescein angiography, FAF, and SD OCT Mantel et al (2018) 38 Color fundus photography, fluorescein angiography, FAF, and SD OCT 13 Cohort study within CATT (N ¼ 1030; patients who completed 2 yrs of follow-up)…”
Section: Ivanmentioning
confidence: 99%
“…A post hoc analysis of RESPONSE (Genetics in Nonresponse to Anti-VEGF Treatment in Exudative AMD [RESPONSE]; ClinicalTrials.gov identifier: NCT01213667) assessed atrophy using CFP, FA, SD OCT, fundus autofluorescence (FAF), and infrared imaging. 28 Retinal pigmented epithelium atrophy (RPEA) developed in 21.2%, 28.8%, 40.4%, 44.2%, and 57.7% of patients at 6 months, year 1, year 2, year 3, and the final visit, respectively. Baseline central retina thickness was the only significant predictor of RPEA development.…”
Section: Responsementioning
confidence: 99%
“…The reported figures show that the highest MA incidence was within the first year of the study. Thavikulwat et al [40], Sadda et al [27], Li et al [47] and Sitnilska et al [48] reported percentages of MA incidence within the first year of 85%, 75%, 65% and 50%, respectively. Over a follow-up period of 4 years, Domalpally also noted that most new occurrences of MA were within the initial 2 years [49].…”
Section: Ma Incidencementioning
confidence: 99%
“…For some studies the expressed percentage was out of the group of study eyes that had no atrophy at the start of the study, whilst for others it was out of the whole cohort of study eyes. For some studies, eyes with baseline MA were excluded from either the analysis or from the whole study [14,21,27,35,36,40,46,48,51], others excluded eyes that did not develop MA by the end of the study [50], while the majority of the remaining reports included eyes with and without MA at baseline and also with and without MA at end of study.…”
Section: Ma Incidencementioning
confidence: 99%
See 1 more Smart Citation